Genetic polymorphism and phenotypic resistance of Mycobacterium tuberculosis to ofloxacin and moxifloxacin - D. V. Vаkhrushevа; T. V. Umpelevа; N. I. Eremeevа; L. S. Lаvrenchuk; S. Yu. Krаsnoborovа; А. E. Panova (Туберкулез и болезни лёгких)
The objective: to study the phenotypic sensitivity of Mycobacterium tuberculosis (MTB) to fluoroquinolones, ofloxacin and moxifloxacin and correlate it with MTB genome mutations associated with resistance to fluoroquinolones to determine the possibility to use these data when compiling chemotherapy regimens IV and V.Subjects and methods. The study included 108 multiple drug resistant Mycobacterium tuberculosis cultures obtained in 2018-2019 from specimens of tuberculosis patients from three regions of Russia.To test drug susceptibility of the isolated cultures, standard methods of the modified method of proportions on a liquid medium by Bactec MGIT 960 were used. Genetic determinants of multiple and extensive drug resistance of tuberculosis mycobacteria were detected using the test system of TB-TEST, OOO Biochip-IMB.Results. Of 66 cultures resistant to ofloxacin, 26 (39.4%) were found to be sensitive to moxifloxacin, while 40 (60.6%) were resistant. Thus, the interpolation of data of ofloxacin drug susceptibility testing to moxifloxacin is unjustified, and using the absolute concentration method as the only phenotypic drug susceptibility testing method in modern laboratories is unacceptable. It was demonstrated that the high level of resistance to moxifloxacin (0.5 μg/ml) was mainly due to the presence of the gyrAD94G, gyrAD94N, and gyrAD94H substitutions in the genome. It was suggested to revise the existing concentrations for moxifloxacin during phenotypic drug susceptibility testing.